A Facile Pre-Lithiated Strategy towards High-Performance Li2Se-LiTiO2 Composite Cathode for Li-Se Batteries - Yang Xia; Zheng Fang; Chengwei Lu; Zhen Xiao; Xinping He; Yongping Gan; Hui Huang; Guoguang Wang; Wenkui Zhang (Nanomaterials, 2022)
Conventional lithium-ion batteries with a limited energy density are unable to assume the responsibility of energy-structure innovation. Lithium-selenium (Li-Se) batteries are considered to be the next generation energy storage devices since Se cathodes have high volumetric energy density. However, the shuttle effect and volume expansion of Se cathodes severely restrict the commercialization of Li-Se batteries. Herein, a facile solid-phase synthesis method is successfully developed to fabricate novel pre-lithiated Li2Se-LiTiO2 composite cathode materials. Impressively, the rationally designed Li2Se-LiTiO2 composites demonstrate significantly enhanced electrochemical performance. On the one hand, the overpotential of Li2Se-LiTiO2 cathode extremely decreases from 2.93 V to 2.15 V. On the other hand, the specific discharge capacity of Li2Se-LiTiO2 cathode is two times higher than that of Li2Se. Such enhancement is mainly accounted to the emergence of oxygen vacancies during the conversion of Ti4+ into Ti3+, as well as the strong chemisorption of LiTiO2 particles for polyselenides. This facile pre-lithiated strategy underscores the potential importance of embedding Li into Se for boosting electrochemical performance of Se cathode, which is highly expected for high-performance Li-Se batteries to cover a wide range of practical applications.